HUBUNGAN SIDIK BIBIR DAN TUNGKAI ATAS DENGAN JENIS KELAMIN PADA SUKU MINANG IKATAN KELUARGA SUMATERA BARAT (IKSB) KOTA BATAM - Rusdani; Rini Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Forensic identification is important to know about people identity like gender. Cheiloscopy is forensic investigation technique based on pattern lip print. Personal identification of based on human bone findings is so important on anthropology. one of it is the length of femur because femur length can be relied to determine human gender.The methode of this research was observational analytic and the number of population was 96 people of minang ethnic group, 48 men and 48 women above 20 years old. Took their lip print by using lipstick methode. After that classified their lip print based on Suzuki-Tsuchihashi and measured their femur length by using left leg.The result showed that Type II men was dominant (37,5%, 47,9%, 35,4%, and 33,3%). In the women side Type I was dominant in quadrant I, III, and IV (29,2%, 45,8%, and 43,8%¬) and Type IV was dominant in quadran II (39,6%). The statistic tested using Chi square alternative test which is Kolmogorov-Smirnov test was P≤0,05 in quadrant II, III, and IV, P≥0,05 in quadrant I. In the other hand for the length of femur, the average of it was men (42,02 cm) longer than women (38,60 cm). When tested with Mann Whitney test got a significant value P≤0,05.Lip print be able to identify personal and gender identification because the unique individual characteristic. And the length of femur be able to identify gender because there was a differentiation on the average between men and women